Interspecific hybridization to introduce useful genetic variability for pigeonpea improvement - Sharma, Shivali; Upadhyaya, H.D. (The Indian Journal of Genetics and Plant Breeding, 2017)
Pigeonpea (Cajanus cajan (L.) Millspaugh) is an important grain legume grown in tropical and subtropical regions of the world. Narrow genetic base coupled with low levels of resistance against important biotic/abiotic stresses in cultivated pigeonpea is the major constraint affecting its production and productivity globally. Wild Cajanus speciesare the reservoir of many important genes including resistance/tolerance to diseases, insect-pests and drought,and good agronomic traits and can be utilized to improve the crop cultivars, enrich variability, and broaden thegenetic base. Utilization of wild Cajanus species hascontributed for the development of cytoplasmic malesterility (CMS) systems for pigeonpea improvement. Prebreeding populations involving promising wild Cajanusaccessions belonging to secondary and tertiary gene poolsas donors and popular pigeonpea cultivars as recipientswere developed for enriching variability for pigeonpeaimprovement. Considerable variability was observed in thesepopulations for morpho-agronomic traits and for bioticstresses. Two advanced backcross populations derivedfrom wild Cajanus species are being genotyped to identifyQTLs associated with agronomic traits for furtherdeployment in pigeonpea improvement programs.Agronomically desirable and disease resistant introgressionlines have been identified and shared with breedingprograms for developing new high-yielding and climateresilient pigeonpea cultivars with a broad genetic base.